BUDAYA UNU TANAH DAN BUDAYA LIO : MENYOAL NARASI MITOS TANAH, HERMENEUTIKA ALAM, DAN KOMUNIKASI LINTAS GENERASI - Nevrettia Christantyawati; Lesman Walensa; Rodrick Stefanus Juraman (Universitas Gadjah Mada, 2018)
This article discusses some studies on the culture of the soil in East Nusa Tenggara and mythical myths that are still perpetuated. The findings from research studies will be generalized by using natural hermeneutics. Myth has always been a fundamental meaning of a symbol of community life, eventhough modern technology has become another option. Some communities still maintain the tradition of using crooks and household appliances from traditional pottery. The myths that live in this society still grow and continue to be preserved through intergenerational communication as part of their bond with nature.